2018
DOI: 10.1111/his.13757
|View full text |Cite
|
Sign up to set email alerts
|

SOX11: a potentially useful marker in surgical pathology: a systematic analysis of SOX11 expression in epithelial and non‐epithelial tumours

Abstract: SOX11 showed prominent expression in neuroectodermal tumours with neural differentiation, high grade-NEC, SDC, rhabdomyosarcoma and MRCL. The high sensitivity and specificity of SOX11 in SDC and MRCL make it a useful diagnostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…48 However, SOX11 expression has only been detected in 1 of 339 DLBCLs investigated in 5 previous studies. [49][50][51][52][53] Therefore, the very rare expression of SOX11 in DLBCL and the common expression of SOX11 in MCL together with the classic or blastoid MCL morphology, CD5 expression, and the aggressive clinical course in our cases favor the closer relationship of these CCNE 1 cases with MCL rather than DLBCL. Further studies are needed to confirm the most appropriate taxonomy of these uncommon cases.…”
Section: Discussionmentioning
confidence: 97%
“…48 However, SOX11 expression has only been detected in 1 of 339 DLBCLs investigated in 5 previous studies. [49][50][51][52][53] Therefore, the very rare expression of SOX11 in DLBCL and the common expression of SOX11 in MCL together with the classic or blastoid MCL morphology, CD5 expression, and the aggressive clinical course in our cases favor the closer relationship of these CCNE 1 cases with MCL rather than DLBCL. Further studies are needed to confirm the most appropriate taxonomy of these uncommon cases.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study found a significant expression of SOX11 in SCLC (68%) [ 19 ]. SOX11 appears to be a valuable diagnostic and prognostic marker for aggressive neuroendocrine tumors [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, continued studies are needed to identify additional NE biomarkers. Our previous publication revealed that transcriptional factor SOX11 downstream of ASCL1 is expressed in high percentages of HG-NECs, particularly SCLCs [ 20 ]. In this study, we further compared SOX11 expression with other NE markers in different kinds of pulmonary carcinomas to access its diagnostic value, and found that SOX11 is a sensitive and more specific NE marker and can be a complement for diagnosis of HG-NECs.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study revealed that SOX11 mRNA expression is significantly upregulated in SCLC and LCNEC and absent expression of SOX11 is correlated with prolonged survival [ 19 ]. In our recent publication we have already found that a high percentage of HG-NECs, particularly SCLCs, were immunopositive for SOX11 [ 20 ]. However, no extensive study comparing the expression of SOX11 with other common NE markers in pulmonary tumors has been reported so far.…”
Section: Introductionmentioning
confidence: 99%